세포 함유 젤라틴 파이버 응용을 통한 골 재생 유도용 인산칼슘 생체재료 세포 탑재 연구 - 김선화; 황창모; 박상혁; Kim, Seon-Hwa; Hwang, Changmo; Park, Sang-Hyug (Journal of biomedical engineering research, 2022)
Natural and synthetic forms of calcium phosphate cement (CPC) have been widely used in bone repair and augmentation. The major challenge of injectable CPC is to deliver the cells without cell death in order to regenerate new bone. The study objective was to investigate for the potential of stem cell-laden gelatin fibers containing injectable, nanocrystalline CPC to function as a delivery system. Gelatin noddle fiber method was developed to delivered cells into nCPC. Experimental groups were prepared by mixing cells with nCPC, mixing cell-laden gelatin fibers with nCPC and mixing cell-laden gelatin fibers containing BMP-2 with nCPC. Media diffusion test was conducted after dissolving the gelatin fibers. SEM examined the generated channels and delivered cell morphology. Fibers mixed with nCPC showed physical setting and hardening within 20 min after injection and showed good shape maintenances. The gelatin fibers mixed nCPC group had several vacant channels generated from the dissolved gelatin. Particularly, proliferation and attachment of the cells were observed inside of the channels. While live cells were not observed in the cell mixed nCPC group, cells delivered with the gelatin fibers into the nCPC showed good viability and increased DNA content with culture. Cell-laden gelatin fiber was a novel method for cell delivery into nCPC without cell damages. Results also indicated the osteogenic differentiation of gelatin fiber delivered cells. We suggest that the cell-laden gelatin fibers mixed with nCPC can be used as an injectable cell delivery vehicle and the addition of BMP-2 to enhances osteogenesis.